Cerebellar Cystic Hemangioblastoma: Case Report - Akdemir, İsmail; Erol, Fatih S.; Tiftikçi, Murat; İçke, M. Uğur; Çobanoğlu, Bengü (Fırat University, 2001)
Thirty-seven-year old woman was admitted to the hospital with the complaint of headache, nausea and vomiting. There were left sided nistagmus and papilledema on neurological examination. A cystic lesion with mural nodule enhancing contrast medium was found on computed tomography (CT). Acute hydrocephalia was characterized by dilatation of the forth, third, and lateral ventricles. The cyst was drained through left sided suboccipital craniectomy and the mural nodule was removed totally. The histopathological examination revealed hemangioblastoma. There was no recurrence on 2-years follow-up CT. We stress on the importance of hemangioblastoma in differential diagnosis of posterior fossa cystic lesions, and discuss the surgical treatment principles of the cystic hemangioblastomas.

Otuz yedi yaşında bayan hasta baş ağrısı, bulantı, kusma ile başvurdu. Yapılan muayenesinde sola bakışta nistagmus, papilödem bulundu. Bilgisayarlı beyin tomografisinde (BBT) kontrast tutan mural nodüllü kistik yapı görüldü. Lezyon üçüncü dördüncü ve lateral ventriküllerde akut obstrüktif hidrosefaliye neden olmakta idi. Sol suboksipital kraniyektomi ile kist drene edilip mural nodül total olarak çıkarıldı. Kitlenin histopatolojik incelenmesinde hemanjioblostom tespit edildi. İki yıl sonraki kontrolünde lezyonda nüks görülmedi. Olgumuz nedeniyle posterior fossadaki kistik lezyonların ayırıcı tanısında hemanjioblastomun dikkate alınmasını ve kistik hemanjioblastomda cerrahi tedavi prensiplerini tartışıyoruz.
SEREBELLAR KİSTİK HEMANJİOBLASTOM: VAKA TAKDİMİ